PENERAPAN MANAJEMEN PERSEDIAAN DALAM MENGANTISPASI KERUGIAN BARANG DAGANGAN DI TOKO MEGA JILBAB - Haslinda; A. Sri Iriani; Muhammad Ardi; Zulkifli (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2020)
This study aims to determine the application of merchandise inventory management and to determine the efforts made in anticipating the loss of merchandise at Mega Jilbab Stores. The type of research used is field research using a qualitative approach and as a source of informants in this study, namely the owner of the Mega Jilbab and the Employees. The results showed that the Mega Jilbab Shop had not implemented inventory management optimally. This can be seen from the absence of special consideration by the owner in providing merchandise that will be marketed on weekdays. The owner only considers the needs of the community which are expected to increase ahead of holidays such as Eid al-Fitr and Eid al-Adha, where the owner provides a larger number of goods than usual. To re-order, the owner orders goods from the Mega Jilbab Shop which is a branch businesses that produce goods and for goods that cannot be produced independently, the owner orders goods at the sultan's shop Tanah Abang Jakarta